Single-Site Robotic Radical Hysterectomy and Sentinel Lymphnode Biopsy in Cervical Cancer: A Case Report - Alexandre Silva e Silva; Rodrigo Pinto Fernandes; Marcia Pereira de Araujo; João Paulo Mancusi de Carvalho; Filomena Marino Carvalho; Giovani Mastrantônio Favero; Jesus Paula Carvalho (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
ABSTRACT Robotic surgeries for cervical cancer have several advantages compared with lapa-rotomic or laparoscopic surgeries. Robotic single-site surgery has many advantages compared with the multiport approach, but its safety and feasibility are not established in radical oncologic surgeries. We report a case of a Federation of Gynecology and Obstetrics (FIGO) stage IB1 cervical carcinoma whose radical hysterectomy, sentinel lymph node mapping, and lymph node dissection were entirely performed by robotic single-site approach. The patient recovered very well, and was discharged from the hospital within 24 hours.